Influence of sinusoidal flow on the thermal and hydraulic performance of microchannel heat sink - Om N.I.; Gunnasegaran P.; Rajasegaran S. (Institute of Physics Publishing, 2023)
In this paper, the effect of sinusoidal flow on the thermal and hydraulic performance of microchannel heat sink (MCHS) is numerically investigated. This investigation covers Reynolds number in the range of 100 ? Re ? 1000 and pure water is used as a working fluid. The three-dimensional steady, laminar flow and heat transfer governing equations are solved using finite volume method (FVM). The water flow field and heat transfer performance inside the sinusoidal microchannels is simulated and the results are compared with the straight microchannels. The effect of using sinusoidal microchannels on temperature distribution, Nusselt number, friction factor and thermal resistance is presented in this paper. It is found that with same rectangular cross-section, sinusoidal microchannels have a better heat transfer performance compared to the straight microchannels. Published under licence by IOP Publishing Ltd.